INTONATION AND PRAGMATICS - THE LOCAL BAHDINANI DIALECT AS AN EXAMPLE - Mousa, Berevan; Musa, Abdulwahab (Humanities Journal of University of Zakho, 2025)
This research, titled "Intonation and Pragmatics: A Study of the Behdinani Local Dialect," analyzes speech from both phonetic and pragmatic perspectives, focusing on the use of intonation among Kurdish speakers of the Behdinani dialect. The study explores how intonation acts as a factor in changing meaning and conveying the speaker’s intention based on the context of the conversation. To achieve more accurate results, the research utilizes the Praat software for analysis. Intonation plays a crucial role in conveying intended meaning. Any change in intonation patterns during speech can lead to difficulties in delivering the pragmatic meaning. The study highlights how rising intonation, falling intonation, and pitch variations in declarative, interrogative, and imperative sentences can alter the type and intended meaning of these sentences. The primary goal of this research is to demonstrate the role of intonation in conveying intended meanings and organizing new information in speech. The research is based on the British scientific research method, specifically the approach of Halliday and Rog, to analyze the intonation of selected sentences in speech from both phonetic and pragmatic perspectives. The study shows that speakers can determine the intended function of their speech by adjusting the pitch of their voice. By changing intonation, speakers can alter the content of their message. For example, changing from rising to rising-falling intonation can shift a sentence from declarative to interrogative. Intonation serves as a key factor in removing ambiguity in speech and determining the speaker’s intention. To achieve this, the researcher provided necessary examples and analyzed them using Praat software.